2015
DOI: 10.5152/akd.2014.5277
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue thickness is associated with myocardial infarction and impaired coronary perfusion

Abstract: Objective:Epicardial adipose tissue (EAT) is associated with the presence, severity and extent of atherosclerotic coronary artery disease (CAD) in addition to subclinical atherosclerosis. We investigated if EAT thickness is related to acute myocardial infarction in patients with CAD. We also searched for the association between EAT thickness and objective coronary flow and myocardial perfusion parameters such as Thrombolysis in Myocardial Infarction Frame count (TFC) and myocardial blush grade (MBG).Methods:Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant coronary artery stenosis, and healthy individuals had a significantly lower EFV compared to the case lot (p <0.001). showed that patients with AMI have a significantly higher EAT thickness compared to unstable angina or stable CAD patients (p <0.001) 39 (Table 5).…”
Section: Eat and Acs Risk Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…6 It is well-known that in the period following an acute myocardial infarction, an exacerbated inflammation is responsible for worse outcomes and ventricular remodeling. 6,16,17 To what extent is this the result of the local release of inflammatory mediators from the area surrounding the infarcted tissue, as well as the link between local activity of the epicardial fat and atrial remodeling in AF, remains to be established.…”
Section: Eat-mediated Inflammation As a Major Player In Cvdmentioning
confidence: 99%